Operational research : IO 2013 - XVI Congress of APDIO, Bragança, Portugal, June 3--5, 2013 /: IO 2013 - XVI Congress of APDIO, Bragança, Portugal, June 3--5, 2013. (2015) - Unknown
No abstract available